Por entre as águas do sertão : currículo & educação ambiental das escolas rurais do Jalapão - Melo, José Carlos de (2011)
This study aimed to give voice to teachers working in rural schools in three municipalities in the Jalapão region in the state of Tocantins (Mateiros, Ponte Alta do Tocantins and São Félix do Tocantins) in relation to the school curriculum and the introduction of the theme of environmental education within that curriculum. The study also sought to understand how public policies are being developed/designed for these schools through the voices of the municipal education secretaries and directors of education responsible for the rural schools of these municipalities. The micro-region of Jalapão is located in the eastern part of the state of Tocantins, on the border with the states of Maranhão, Piauí and Bahia. It is an area totaling 53,300 km2, and of this total 34,100 km2 lies within the state of Tocantins. In terms of data collection, questionnaires were sent to the teachers and a check-list was sent to the secretaries and directors of education working in the secretariats of municipal education. The research identified in the voices of teachers, all of whom work in rural schools and teach students of several levels together, the suffering caused by the lack of teaching material and infrastructure necessary to develop the issue of the environment - which in turn is not in the curricula proposals of these schools. It was also noted that there still does not exist a public policy to introduce this issue on the part of the local authorities, leaving it to the teachers to develop these activities, which often occurs in an individualistic manner. Thus, in dealing with the subject of the environment, the voices of teachers and the public authorities reveal that schools should consider social, economical and cultural human rights in relation to the environment and seek to establish goals for cultural development, quality of life and sustainable environmental balance especially in the case of rural schools